2015
DOI: 10.5014/ajot.2015.017855
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions for Children With Autism Spectrum Disorder and Their Parents: A Systematic Review of Family Outcomes

Abstract: This systematic review examined the literature published from January 2006 to April 2013 related to the effectiveness of occupational therapy interventions for children with autism spectrum disorder (ASD) and their parents to improve parental stress and self-efficacy, coping, and resilience and family participation in daily life and routines. From the 4,457 abstracts, 34 articles were selected that matched the inclusion criteria. The results were mixed and somewhat inconclusive because this body of literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 98 publications
2
37
0
1
Order By: Relevance
“…Evidence suggests that parent-delivered intervention is equally effective to therapist-delivered intervention (Baker et al, 2012), which is not surprising given parent's knowledge of their children's preferences and engagement style, and the volume of caregiving they carryout (Smith, Cheater & Bekker, 2015). In the diagnoses studied (ADHD, ASD, At risk, Behavioural Disorders, BI, CP, DD, LD, obesity), it was very clear that parents respond well to parent education and training Barlow, Smailagic, Huband, Roloff & Bennett, 2012;Case-Smith & Arbesman, 2008;Dykens, Fisher, Taylor, Lambert & Miodrag, 2014;Feinberg et al, 2014;Hanna & Rodger, 2002;Howe & Wang, 2013;Kuhaneck, Madonna, Novak & Pearson, 2015;Lawler, Taylor & Shields, 2013;Tanner, Hand, O'toole & Lane, 2015;Zwi, Jones, Thorgaard, York & Dennis, 2011), consistent with family centred philosophy about parents' aspirations of parenting well, to help their children (Hanna & Rodger, 2002). Moreover, parents and children carry out intervention effectively at home, and therefore home programs (Novak & Berry, 2014b;Sakzewski, Ziviani & Boyd, 2013;Sakzewski et al, 2015;Wuang, Ho & Su, 2013) and selfmanagement programs (Lindsay, Kingsnorth, Mcdougall & Keating, 2014;Moola, Faulkner, White & Kirsh, 2014) are an effective method for increasing the intensity of therapy.…”
Section: A Parent Partnership Within Occupational Therapist Intervenmentioning
confidence: 94%
“…Evidence suggests that parent-delivered intervention is equally effective to therapist-delivered intervention (Baker et al, 2012), which is not surprising given parent's knowledge of their children's preferences and engagement style, and the volume of caregiving they carryout (Smith, Cheater & Bekker, 2015). In the diagnoses studied (ADHD, ASD, At risk, Behavioural Disorders, BI, CP, DD, LD, obesity), it was very clear that parents respond well to parent education and training Barlow, Smailagic, Huband, Roloff & Bennett, 2012;Case-Smith & Arbesman, 2008;Dykens, Fisher, Taylor, Lambert & Miodrag, 2014;Feinberg et al, 2014;Hanna & Rodger, 2002;Howe & Wang, 2013;Kuhaneck, Madonna, Novak & Pearson, 2015;Lawler, Taylor & Shields, 2013;Tanner, Hand, O'toole & Lane, 2015;Zwi, Jones, Thorgaard, York & Dennis, 2011), consistent with family centred philosophy about parents' aspirations of parenting well, to help their children (Hanna & Rodger, 2002). Moreover, parents and children carry out intervention effectively at home, and therefore home programs (Novak & Berry, 2014b;Sakzewski, Ziviani & Boyd, 2013;Sakzewski et al, 2015;Wuang, Ho & Su, 2013) and selfmanagement programs (Lindsay, Kingsnorth, Mcdougall & Keating, 2014;Moola, Faulkner, White & Kirsh, 2014) are an effective method for increasing the intensity of therapy.…”
Section: A Parent Partnership Within Occupational Therapist Intervenmentioning
confidence: 94%
“…While early interventions are important, research has shown that interventions for children with ASD and their parents can also increase the level of stress in parents,18 which may in turn reduce the effectiveness of the interventions given 19. Thus, children with ASD and other developmental problems in the field of ESSENCE need continuous support, monitoring, and adjustments in their everyday life for a positive development 20…”
Section: Introductionmentioning
confidence: 99%
“…These skills are essential as the PCG is a constant figure who provides the physical, emotional, material, social, and therapy needs of the child (Bruder, 2000). Interventions providing the "know how" for PCG were in keeping with the needs of a CASD such as addressing skills needed to manage activities of daily living, communication, development, and behaviour (Davis & Carter, 2014;Kuhaneck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Development and activity was noted in the practical skills taught to PCG who are required to fulfil the daily tasks and activities of their CASD (McStay et al, 2014). Similarly, the domain of emotional well-being was noted in the supportive activities provided to PCG to minimise the effects of the emotional strain PCG experience in raising a CASD (Davis & Carter, 2014;Kuhaneck et al, 2015). Fewer studies addressed social well-being which is contrary to the social burden that PCG experience given the incidence of stigma and the social awkwardness that comes with having a CASD (Wang et al, 2012;Woodgate, Ateah, & Secco, 2008).…”
Section: Discussionmentioning
confidence: 99%